Student Perception and Experience with “Talk” - AI-Powered Speaking Partner Application - Dimas Vega Rizqyqa Putra Budiyono; Pramana Rafif; Abdullah Yusuf; Ahmad Syafi’I (Journal of English Language Teaching and Islamic Integration, 2024)
This fact highlights the increasing need for effective and accessible English education. Many schools and educational institutions are now developing modern and innovative methods for teaching English, encompassing both teaching approaches and tools that facilitate learners in enhancing their English language skills (Cong-Lem, 2018). In learning English, there are four essential competencies that must be mastered by the learners. These four competencies are proficiency in reading, listening, writing, and speaking (Pliushchenko & Zaslavskiy, 2021). However, the speaking skill is often considered as the most crucial among the other four abilities. Speaking is one of the most important skills of all four language skills, because individuals who learn a language are referred to as the speakers of that language. The main aim of English language teaching is to give learners the ability to use English language effectively and correctly in communication (Jarrín & Kim, 2019).